Determinación del PH del Agua de Riego para Pastos Proveniente del Canal Latacunga – Salcedo – Ambato y propuesta de regulación. - Telenchana Vargas, Jefferson Alexander (2019)
This researching was applied at the Technical University of Cotopaxi, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, at a height of 2725 m.a.s.l. with 78º37’14 ’’ West longitude and 00º59’57 ’’ South latitude, with the objective of measuring the pH of the irrigation water of the Latacunga - Salcedo - Ambato waterway and making a regulation proposal. A randomized complete block design was applied, giving a total of 12 treatments (pH values) and 3 repetitions performed in the months of February, March and April. The methodology to follow was to take water samples from the waterway in open places from the abscissa 0 + 000 indicating the place of the Bocatoma and tunnel entrance 0 to the abscissa 6 + 875.90 with the 86031 Handheld IP67 Combo PH / COND instrument /SALT/DO that gave us the pH values. The results of the analysis of variance were not significant in any of the sources of variation, the coefficient of variation was 3.08, and indicating that the values were homogeneous and the average was 7.84. Precipitation in the months of February, March and April was 25.5; 48.5 and 71.7 mm respectively. The final pH sampling was performed in the CEASA reservoir where an average value of 8.23 was obtained reaching an alkaline level and the soil analysis obtained reflected a pH value of 8.43 also at the slightly alkaline level; The proposed regulation was the use of citric acid in a dose of 0.5 gl-1 to reach a water pH value of 6.2 suitable for irrigation in the cultivation of alfalfa grass (Medicago sativa).